Rare CYLD Variants in Chinese Patients With Amyotrophic Lateral Sclerosis - Gu, Xiaojing; Chen, Yongping; Wei, Qianqian; Hou, Yanbing; Cao, Bei; Zhang, Lingyu; Ou, Ruwei; Lin, Junyu; Liu, Kuncheng; Zhao, Bi; Shang, Huifang (Frontiers in Genetics, 2021)
Background CYLD Lysine 63 Deubiquitinase gene (CYLD) was recently identified to be a novel causative gene for frontal temporal dementia (FTD)-amyotrophic lateral sclerosis (ALS). In the current study, we aimed to: 1) systematically screen the mutations of CYLD in a large cohort of Chinese ALS patients; 2) study the genotype-phenotype correlation; 3) explore the role of CYLD in ALS via rare variants burden analysis. Methods A total of 978 Chinese sporadic ALS (sALS) patients and 46 familial ALS (fALS) patients were sequenced with whole exome sequencing and analyzed rare variants in CYLD with minor allele frequency <0.1%. Results In total, 7 rare missense variants in CYLD have been identified in 7 (0.72%) patients among 978 sALS patients. And 2 (4.3%) rare missense variants were identified among the 46 fALS cases, in which 1 patient was diagnosed as having comorbidity of ALS and progressive supranuclear palsy(PSP). Moreover, the burden analysis indicated no enrichment of rare variants in CYLD among patients with ALS. Conclusion In conclusion, our study extended the genotype and phenotype of CYLD in ALS, but the pathogenicity of these variants needs to be further verified. Moreover, burden analysis argued against the role of CYLD in the pathogenesis of ALS. More studies from different ethnicities would be needed.